EXAMINING THE IMPLICATION OF TQM, CUSTOMER SATISFACTION, SERVICE QUALITY, AND MARKET ORIENTATION IN PRIVATE BANK IN SURABAYA - Audrey, Evelyn; Sutrisno, Timotius F. C. W. (DeReMa (Development Research of Management): Jurnal Manajemen, 2024)
Total Quality Management (TQM) has gained significant attention across various industries as a concept to enhance organizational performance, including in banking industry. This research paper aims to investigate the implementation and impact of TQM principles in the banking industry, exploring its essential indicators including service quality, market orientation, and customer satisfaction. The study begins by reviewing the existing literature on TQM and its application in the banking industry, highlighting key concepts, methodologies, and discussion. Empirical data was taken from 185 bank workers in East Java Region of the Republic of Indonesia, especially Surabaya City. This study uses Confirmatory Factor Analysis to test construct reliability and validity, while the relationship between variables is examined with Partial Least Square/ PLS-SEM. This research uses purposive sampling, we are targeting private bank workers in Surabaya through online questionnaires spread by social media. This research contributes to the existing body of knowledge by providing a comprehensive review and analysis of TQM implementation in the banking industry. This research findings demonstrate that TQM has a significant relationship with Customer Satisfaction, Service Quality, and Market Orientation.Abstrak dalam Bahasa Indonesia. Manajemen Mutu Total (TQM) telah mendapatkan perhatian signifikan di berbagai industri sebagai konsep untuk meningkatkan kinerja organisasi, termasuk dalam industri perbankan. Makalah penelitian ini bertujuan untuk menyelidiki implementasi dan dampak prinsip-prinsip TQM di industri perbankan, mengeksplorasi indikator-indikator pentingnya termasuk kualitas layanan, orientasi pasar, dan kepuasan pelanggan. Studi ini dimulai dengan meninjau literatur yang ada tentang TQM dan aplikasinya dalam industri perbankan, menyoroti konsep-konsep kunci, metodologi, dan diskusi. Data empiris diambil dari 185 pekerja bank di Wilayah Jawa Timur Republik Indonesia, khususnya Kota Surabaya. Penelitian ini menggunakan Analisis Faktor Konfirmatori untuk menguji reliabilitas dan validitas konstruk, sementara hubungan antar variabel diperiksa dengan Partial Least Square/PLS-SEM. Penelitian ini menggunakan purposive sampling, kami menargetkan pekerja bank swasta di Surabaya melalui kuesioner online yang disebar melalui media sosial. Penemuan penelitian ini berkontribusi pada tubuh pengetahuan yang ada dengan memberikan tinjauan dan analisis yang komprehensif tentang implementasi TQM di industri perbankan. Temuan penelitian ini menunjukkan bahwa TQM memiliki hubungan yang signifikan dengan Kepuasan Pelanggan, Kualitas Layanan, dan Orientasi Pasar.